A prospective study examining the incidence of asymptomatic and symptomatic lymphoceles following lymphadenectomy in patients with gynecological cancer - Zikán, Michal; Fischerová, Daniela; Pinkavová, Ivana; Sláma, Jiří; Weinberger, Vít; Dušek, Ladislav; Cibula, David (Gynecologic oncology, 2015)
OBJECTIVE: To identify the incidence of asymptomatic and symptomatic (i.e., causing pain, hydronephrosis, venous thrombosis, acute lymphedema of the lower or urinary urgency) lymphoceles, as well as risk factors for their development, through a prospective study of patients undergoing sole pelvic or combined pelvic and paraaortic lymphadenectomy for gynecological cancer. METHODS: Patients with endometrial, ovarian or cervical cancer scheduled for sole pelvic or combined pelvic and paraaortic lymphadenectomy as a primary surgical treatment or salvage surgery for recurrence were enrolled at single institution from February 2006 to November 2010 and prospectively followed up with ultrasound. RESULTS: Of 800 patients who underwent sole pelvic or combined pelvic and paraaortic lymphadenectomy for gynecological cancer, the overall incidence of lymphoceles was 20.2%, with symptomatic lymphoceles occurring in 5.8% of all patients. Lymphoceles are predominantly located on the left pelvic side wall. Lymphadenectomy in ovarian cancer, a higher number of lymph nodes obtained (>27), and radical hysterectomy in cervical cancer were found to be independent risk factors for the development of symptomatic lymphoceles. CONCLUSIONS: The overall incidence of lymphocele development after lymphadenectomy for gynecological cancer remains high. However, the majority of lymphoceles are only incidental finding without clinical impact. A symptomatic lymphocele is an uncommon event, occurring in only 5.8% of patients. Symptomatic lymphoceles tend to develop earlier than asymptomatic. Although such risk factors are hard to avoid, patients known to be at an increased risk of developing symptomatic lymphoceles can be counseled appropriately and followed up for specific symptoms relating to lymphocele development.
Keywords: Young Adult; Lymph Node Excision; Risk Factors; lokální recidiva nádoru; mladý dospělý; Lymphocele; Česká republika; lymfokela; Genital Neoplasms, Female; Adult; lymfadenektomie; Aged; dospělí; Prospective Studies; senioři; incidence; Czech Republic; nádory ženských pohlavních orgánů; Neoplasm Recurrence, Local; senioři nad 80 let; lidé; ženské pohlaví; Humans; rizikové faktory; Aged, 80 and over; Female; lidé středního věku; Incidence; Middle Aged; prospektivní studie